2020
DOI: 10.1021/acsenergylett.9b02596
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Butanol Production: From Biocatalysis to Bioelectrocatalysis

Abstract: Butanol from renewable biomass is a promising advanced biofuel that can be used as an optimal substitute for gasoline in the transportation sectors, and therefore, large-scale industrial production of biobutanol has great importance to the development of sustainable energy. However, the low bioproductivity of butanol is a big challenge, despite great progress in metabolic engineering and bioprocessing. More importantly, butanol biosynthesis is mainly a consequence of anaerobic transformations catalyzed by spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 84 publications
0
26
0
Order By: Relevance
“…For example, coating MOF directly onto cell membranes offers a potential shield for cytoprotection, thereby enhancing the adaptability of cells or corresponding biohybrids towards adverse environmental impacts [136]. (2) To promote the conversion of value-added chemicals, exploiting the enzymatic machineries imbedded in native microbial cells might ensure products with exquisite selectivity and circumvent energy/product losses resulting from secondary biomass proliferation [157]. 3To maximize electron flow in clean fuel synthesis, enhancing the electron flux through engineered microbial strains produced by manipulating genetic materials could greatly enhance efficacy (e.g., employing CRISPR [clustered regularly interspaced short palindromic repeats] and CRISPRi [CRISPR interference] technologies) [158,159].…”
Section: Discussionmentioning
confidence: 99%
“…For example, coating MOF directly onto cell membranes offers a potential shield for cytoprotection, thereby enhancing the adaptability of cells or corresponding biohybrids towards adverse environmental impacts [136]. (2) To promote the conversion of value-added chemicals, exploiting the enzymatic machineries imbedded in native microbial cells might ensure products with exquisite selectivity and circumvent energy/product losses resulting from secondary biomass proliferation [157]. 3To maximize electron flow in clean fuel synthesis, enhancing the electron flux through engineered microbial strains produced by manipulating genetic materials could greatly enhance efficacy (e.g., employing CRISPR [clustered regularly interspaced short palindromic repeats] and CRISPRi [CRISPR interference] technologies) [158,159].…”
Section: Discussionmentioning
confidence: 99%
“…Based on these findings, it was found that HBu and HAc were eminently affected by hydrogen production in Equations (2) and (3). The highest range found in butyrate acid proposed that the biohydrogen production from a mixture of xylose and glucose was of a butyrate type in Equation (3).…”
Section: Effect Of Alginate and Chitosan Concentration On Volatile Famentioning
confidence: 94%
“…Dark fermentation is being recognised as an excellent biological method of hydrogen production because of its ability to perform without light energy and oxygen source [2]. Fermentation is the process of using specific microorganisms to convert organic substrates into hydrogen, carbon dioxide, and other solutes such as acetate, butanol, and ethanol [3].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, various alternative sources of energy such as solar, wind, and biomass have attracted attention and are regarded as renewable sources. Among those sources, lignocellulosic biomass has been studied as an important resource that can be converted into liquid transportation fuels (ethanol and butanol) and various industrial biochemical products by utilizing main components of biomass such as cellulose, hemicellulose, and lignin [3][4][5]. In the past, sugar and starch obtained from sugarcane and corn grain have been primary source of fuel ethanol production, termed as the first-generation biomass and fuel, respectively [6].…”
Section: Introductionmentioning
confidence: 99%